Translocation of an immunoglobulin kappa locus to a region 3' of an unrearranged c-myc oncogene enhances c-myc transcription. - Erikson, J (1983)
We have studied somatic cell hybrids between mouse myeloma and JI Burkitt lymphoma cells carrying a t(2;8) chromosome translocation for the expression of human kappa chains. and for the presence and rearrangements of the human c-myc oncogene and kappa chain genes. Our results indicate that the c-myc oncogene is unrearranged and remains on the 8q+ chromosome of JI cells. Two rearranged C kappa genes were detected: the expressed allele on normal chromosome 2 and the excluded kappa allele that was translocated from chromosome 2 to the involved chromosome 8 (8q+). The distribution of V kappa and C kappa genes in hybrid clones retaining different human chromosomes indicated that C kappa is distal to V kappa on 2p and that the breakpoint in this Burkitt lymphoma is within the region carrying V kappa genes. High levels of transcripts of the c-myc gene were found when it resided on the 8q+ chromosome but not on the normal chromosome 8, demonstrating that translocation of a kappa locus to region distal to the c-myc oncogene enhances c-myc transcription.